Arts-based research across textual media in education : expanding visual epistemology (New York, NY : Routledge, 2024)
"In company with its sister volume, Arts-Based Research Across Textual Media in Education explores arts-based approaches to research across media, including film and comics-related material, from a variety of geographic locations and across a range of sub-disciplines within the field of education. This first volume takes a textual focus, capturing process, poetic, and dramaturgical approaches. The authors aim to highlight some of the approaches that are not always centered in arts-based research. The contributors represent a variety of arts-based practices and methods, and they weave this marrying of artistic and scientific expertise and experience into the fabric of the chapters themselves. Authors from international contexts speak to the importance of utilizing artistic approaches for research processes. From multimodal field notes to poetic forms to the dramaturgical, chapters in this book represent steps forward in educational inquiry to bringing together both the creative and credible. The book includes multiple images and rich descriptions shared from the field. This first volume covers amongst other topics: co-created narratives; creative fiction in research; analytic portraits; dramatic representation, and critical poetic inquiry. It would be suitable for graduate students and scholars interested in qualitative inquiry and arts-based methods, in Education and the social sciences"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Education -- Research -- Methodology; Qualitative research -- Methodology; Mass media -- Research -- Methodology; Arts in education; Mass media and education; Science and the arts